The effect of incorporating coordination exercises into the physical education lesson plan on developing sensory-motor coordination and some biomotor abilities among fifth-grade elementary school students - Abdullah, L. Hassanein Jawad; continues, L. Iman Darwish; Saleh, Prof. Dr. Hasim Abdul Jabbar; Saleh, Prof. Dr. Thaera Abdul Jabbar (Sulaimani Journal for Humanities, 2026)
The importance of this research lies in identifying the extent to which incorporating coordination exercises into physical education lesson plans contributes to the development of sensory-motor coordination, as well as the role of coordination exercises in the biomechanical abilities of fifth-grade students. Given that the researchers work in both the educational and scientific fields, they observed a weakness in the use of coordination exercises in physical education lessons. Physical education lesson plans are often limited to the standard curriculum used by teachers and emphasized by physical education supervisors. Furthermore, there is a lack of attention to the physical aspect due to insufficient focus on this age group. In addition to teachers' reliance on traditional exercises and their avoidance of modern teaching methods and techniques, the age group studied by the researchers is young and requires significantly more effort than older students. This age group needs to develop specific biomotor abilities and fundamental skills to reach a high level, and achieving these results requires a longer period of time. The use of coordination exercises plays a crucial role in the training and educational process, especially for young children. Therefore, the researchers decided to incorporate coordination exercises to develop sensory-motor coordination and biomotor abilities, and to observe their effects in the physical education curriculum for fifth grade, with the aim of improving the students' physical, motor, and mental performance. The research aims to: - Develop coordination exercises for fifth-grade students. - Integrate the developed coordination exercises into the physical education curriculum for fifth-grade students. - Identify the impact of coordination exercises on sensory-motor coordination and certain biomotor abilities among fifth-grade students. The researchers used a two-group experimental design with pre- and post-testing, as it was suitable for the nature of the problem under study. The researchers defined the research population as fifth-grade students at Khair Al-Bariya School in Karbala Governorate, consisting of two classes of 40 students each. Sixty students were selected as the research sample and randomly divided equally into two groups: an experimental group and a control group of 30 students each. The first group used the standard physical education lesson plan followed in all schools, while the second group used coordination exercises within the same physical education lesson plan.